2010
DOI: 10.1002/col.20570
|View full text |Cite
|
Sign up to set email alerts
|

Influences of psychological factors on image color preferences evaluation

Abstract: To bring substantial benefits of image designing for image designers and image processing professionals, this study focused on the image samples taken by digital cameras and tried to explore the influence of psychological factors on image color preference. First, we collected 310 questionnaires to investigate the types of image that interest the people in Taiwan. The images that Taiwanese prefer were categorized into seven types: People, Scenery, Artificial Environment, Plants, Animals, Still Life, and Food. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results showed that different colors can significantly influence response time and error rate, which suggests that color has a distinct influence on impulsiveness and arousal. In terms of saturation, Guan et al conducted a survey that revealed the relationship between six image color preferences and psychological factors, such as color saturation 10 …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that different colors can significantly influence response time and error rate, which suggests that color has a distinct influence on impulsiveness and arousal. In terms of saturation, Guan et al conducted a survey that revealed the relationship between six image color preferences and psychological factors, such as color saturation 10 …”
Section: Introductionmentioning
confidence: 99%